2001
DOI: 10.1103/physrevb.63.235201
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature ultrafast carrier and spin dynamics in GaAs probed by the photoinduced magneto-optical Kerr effect

Abstract: The picosecond and subpicosecond dynamics of spins in intrinsic and n-doped GaAs is investigated at room temperature using the time-resolved, pump and probe, photoinduced, near-resonant magneto-optical Kerr effect between 1.44 and 1.63 eV. Three components with different temporal and spectral behavior are distinguished in both Kerr rotation and ellipticity, and their origin is discussed in relation with theoretical predictions and simulations. Two contributions are attributed to the splitting of the spin suble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
1
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(78 citation statements)
references
References 31 publications
6
67
1
4
Order By: Relevance
“…Our rotation measurements do not fully characterize the cubic susceptibility tensor, only the combination of components given in equations (4) and (5). From figures 4, 6 and 8 we might conclude that the SIFE dominates the zero-delay peak in GaAs [7], the SOKE is dominant in Al, while the more complicated dependence in Ni is the result of competition between the SIFE and the SOKE. No comprehensive microscopic theory of the cubic non-linearity has yet been advanced, and there is no reason to expect that similar behaviour should be observed in GaAs, Ni and Al, given their very different electronic structures.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our rotation measurements do not fully characterize the cubic susceptibility tensor, only the combination of components given in equations (4) and (5). From figures 4, 6 and 8 we might conclude that the SIFE dominates the zero-delay peak in GaAs [7], the SOKE is dominant in Al, while the more complicated dependence in Ni is the result of competition between the SIFE and the SOKE. No comprehensive microscopic theory of the cubic non-linearity has yet been advanced, and there is no reason to expect that similar behaviour should be observed in GaAs, Ni and Al, given their very different electronic structures.…”
Section: Discussionmentioning
confidence: 92%
“…The form of the expected magneto-optical response may be obtained by convolving the functional form of each expected component (a δ function and two exponentials) with the pump and probe pulse profiles. This yields the following expression [7]:…”
Section: Gallium Arsenidementioning
confidence: 99%
“…The spin-relaxation time varies from somewhat less than 100 ps for wide quantum wells, approximating the bulk data (cf. Kimel et al, 2001, where 15 psϽ s Ͻ35 ps was found for a heavily doped n-GaAs), to about 10 ps in most confined structures. The downturn for the highest-E 1 well (of width 3 nm) is most likely due to the increased importance of interface roughness at such small widths (Malinowski et al, 2000).…”
Section: B Gaas-based Quantum Wellsmentioning
confidence: 99%
“…The answer will certainly depend on N d . Recent experiments on time-resolved Kerr rotation (Kimel et al, 2001) suggest that 5 psϽ s Ͻ10 ps for undoped GaAs and 15 psϽ s Ͻ35 ps for a heavily doped n-GaAs with N d ϭ2ϫ10 18 cm Ϫ3 .…”
Section: A Bulk N-gaasmentioning
confidence: 99%
“…For a more systematic analysis the temporal dependencies measured at different photon energies were fitted as a sum of two exponential decays with characteristic times 1 7 and 2 30 ps and different amplitudes I 1 and I 2 [21], respectively, i.e.,…”
mentioning
confidence: 99%